2008
DOI: 10.1055/s-2008-1038887
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Pulmonary Metastases with Helical CT: The Effect of Imaging Techniques

Abstract: We conclude that a reduced slice thickness may have an important positive impact on the treatment and outcome of patients with pulmonary metastases. The use of 3-mm slice thickness helical CT may raise the sensitivity for pulmonary metastases detection compared to 5-mm images, but the rate of false positive results may also increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 9 publications
2
15
0
1
Order By: Relevance
“…Some researchers recommended sternotomy or thoracotomy1. Studies of these conventional procedures have found that the sensitivity of helical CT in detection of pulmonary metastatic lesions varies from 77% to 88.3% (Table 4)91416171819. The corresponding figure in our study was 63%.…”
Section: Discussionsupporting
confidence: 53%
“…Some researchers recommended sternotomy or thoracotomy1. Studies of these conventional procedures have found that the sensitivity of helical CT in detection of pulmonary metastatic lesions varies from 77% to 88.3% (Table 4)91416171819. The corresponding figure in our study was 63%.…”
Section: Discussionsupporting
confidence: 53%
“…Currently, computed tomography (CT) is used to detect recurrence; however, it has a high falsenegative rate for extrahepatic intra-abdominal lesions (e.g., para-aortic nodes) and a high false-positive rate for pulmonary lesions [9,10]. This disadvantage has led to the increased use of 18F-fluorodeoxyglucose (18F-FDG)-positron emission tomography (PET)/CT as an imaging modality, in both preoperative assessment and during follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Another way to increase detection is decreasing the slice thickness. Reducing the slice thickness from 5 mm to 3 mm results in a significant increase in the detection of lesions (7). It could be postulated that the identification of more lesions would limit the usefulness of bimanual lung palpation during operation, but with the decrease in sensitivity with smaller lesions, palpation may detect lesions missed by preoperative CT.…”
Section: Radiographic Diagnosis and Preoperative Imagingmentioning
confidence: 99%